PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG TIDAK DIBERI UPAH/GAJI DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (Studio PT. Bakrie Construction Sumuranja Banten) - Alvin Agung Wicaksono; Amad Sudiro (Faculty of Law - Tarumanagara University, 2021)
The rapid development of the business world today has created many problems for companies to face. One of the problems faced by most companies is human resources as the executor of the company's production activities. Due to this legal relationship and to avoid arbitrariness, the government has formulated regulations governing interpersonal relationships in the world of work. PT Bakrie Construction is a subsidiary of Bakrie Metal Industries, a subsidiary of Bakrie and Brothers, focuses on the EPC business and its steel factory facilities are located in Sumuranja Bojonegara, PT. Bakrie Construction found a case of not paying salaries to its workers hence violating Indonesia’s labor law where economical work protection is required to be fulfilled by the companies to the labourers in exchange of their labour to the company. Labour laws are needed to help the labourers so they would not be discriminated against by any means like social, economical and technically by the companies that hire them.